Two Hundred Exercises in Mechanistic Organic Chemistry - Suárez, Gabriel Tojo (Cambridge Scholars Publishing, 2021)
This book will strengthen the knowledge of mechanistic organic chemistry for organic chemists who have completed a bachelor's degree and want to start researching in a laboratory or working in a chemical company. Hardly ever does an organic synthesis advance according to plan. Diligently designed synthetic schemes stumble upon the laboratory reality of meagre yields, side reactions, and unwanted products. To fight against that we have a magnificent intellectual tool: reaction mechanisms. In the course of an undergraduate degree, the student assimilates an assortment of unadorned reaction mechani.